1.
SOLVING SYSTEMS
OF EQUATIONS AND
INEQUALITIES
Module 1 Lesson 5
2.
What is a system of equations?
A system of equations is when you have two
or more equations using the same variables.
The solution to the system is the point that
satisfies ALL of the equations. This point will
be an ordered pair.
When graphing, you will encounter three
possibilities.
Consistent Systems (one solution)
Inconsistent Systems (no solutions)
Dependent Systems (Infinite number of
solutions)
3.
Consistent Systems
The lines will intersect.
The point where the lines
intersect is your solution.
The solution of this graph is
(1, 2)
(1,2)
4.
Inconsistent Systems
These lines never
intersect as the lines are
parallel!
Since the lines never
cross, there is
NO SOLUTION!
Parallel lines have the
same slope with different
y-intercepts.
2
=2
1
y-intercept = 2
y-intercept = -1
Slope =
5.
Dependent Systems
These lines are the same!
Since the lines are on top
of each other, there are
INFINITELY MANY
SOLUTIONS!
Coinciding lines have the
same slope and
y-intercepts.
2
=2
1
y-intercept = -1
Slope =
6.
What is the solution of the system
graphed below?
1.
2.
3.
4.
(2, -2)
(-2, 2)
No solution
Infinitely many solutions
7.
1) Find the solution to the following system by
graphing:
2x + y = 4
x-y=2
Graph both equations.
I will graph using x- and y-intercepts (plug in
zeros), but you can also rewrite in to y =mx + b
form.
2x + y = 4
(0, 4) and (2, 0)
x–y=2
(0, -2) and (2, 0)
Graph the ordered pairs.
8.
Graph the equations.
4
Where do the lines intersect?
(2, 0)
y=
x-y=2
(0, -2) and (2, 0)
+
2x
2x + y = 4
(0, 4) and (2, 0)
x–
y=
2
9.
Check your answer!
To check your answer, plug
the point back into both
equations.
2x + y = 4
2(2) + (0) = 4
x-y=2
(2) – (0) = 2
Nice job…let’s try another!
10.
2) Find the solution to the following
system:
y = 2x – 3
-2x + y = 1
Graph both equations. Put both equations in
slope-intercept or standard form. I’ll do slopeintercept form on this one!
y = 2x – 3
y = 2x + 1
Graph using slope and y-intercept
11.
Graph the equations.
y = 2x – 3
m = 2 and b = -3
y = 2x + 1
m = 2 and b = 1
Where do the lines intersect?
No solution!
Notice that the slopes are the same with different
y-intercepts. If you recognize this early, you don’t
have to graph them!
12.
Check your answer!
Not a lot to check…Just
make sure you set up your
equations correctly.
I double-checked it and I did
it right…
13.
What is the solution of this system?
3x – y = 8
2y = 6x -16
1.
2.
3.
4.
(3, 1)
(4, 4)
No solution
Infinitely many solutions
14.
Solving a system of equations by Graphing
Let's summarize! There are 3 steps to solving
a system using a graph.
Step 1: Graph both equations.
Graph using slope and y – intercept
or x- and y-intercepts. Be sure to use
a ruler and graph paper!
Step 2: Do the graphs intersect?
This is the solution! LABEL the
solution!
Step 3: Check your solution.
Substitute the x and y values into
both equations to verify the point is
a solution to both equations.
15.
Solving Systems of Equations
using Subs titutio n
Steps:
1.Solve one equation for one variable (y = ; x = ;
a =)
2.Substitute the expression from step one into
the other equation.
3.Simplify and solve the equation.
4.Substitute back into either original equation to
find the value of the other variable.
5. Check the solution in both equations of the
system.
16.
Example #1:
y = 4x
3x + y = -21
Step 1: Solve one equation for one variable.
y = 4x
(This equation is already solved for y.)
Step 2: Substitute the expression from step one
into
the other equation.
3x + y = -21
3x + 4x = -21
Step 3: Simplify and solve the equation.
7x = -21
x = -3
17.
Example #1 cont:
y = 4x
3x + y = -21
Step 4: Substitute back into either original
equation to find the value of the
other
variable.
3x + y = -21
3(-3) + y = -21
-9 + y = -21
y = -12
Solution to the system is (-3, -12).
18.
y = 4x
3x + y = -21
Step 5: Check the solution in both equations.
Solution to the system is (-3,-12).
y = 4x
3x + y = -21
-12 = 4(-3)
3(-3) + (-12) = -21
-12 = -12
-9 + (-12) = -21
-21= -21
19.
Example #2:
x + y = 10
5x – y = 2
Step 1: Solve one equation for one variable.
x + y = 10
y = -x +10
Step 2: Substitute the expression from step one
into
the other equation.
5x - y = 2
5x -(-x +10) = 2
20.
Example #2 cont:
x + y = 10
5x – y = 2
Step 3: Simplify and solve the equation.
5x -(-x + 10) = 2
5x + x -10 = 2
6x -10 = 2
6x = 12
x=2
21.
Example #2 cont:
x + y = 10
5x – y = 2
Step 4: Substitute back into either original
equation to find the value of the
other
variable.
x + y = 10
2 + y = 10
y =8
Solution to the system is (2,8).
22.
Example #2 cont:
x + y = 10
5x – y = 2
Step 5: Check the solution in both equations.
Solution to the system is (2, 8).
x + y =10
2 + 8 =10
10 =10
5x – y = 2
5(2) - (8) = 2
10 – 8 = 2
2=2
23.
Solving Systems of Equations using
Elimination
(a ls o c a lle d So lving by us ing A d itio n)
d
Steps:
1.Place both equations in Standard Form, Ax + By = C.
2.Determine which variable to eliminate with Addition or
Subtraction.
3.Solve for the variable left.
4.Go back and use the found variable in step 3 to find
second variable.
5. Check the solution in both equations of the system.
24.
EXAMPLE #1:
STEP 1:
form.
STEP 2:
STEP 3:
5x + 3y = 11
5x = 2y + 1
Write both equations in Ax + By = C
5x + 3y =1
5x - 2y =1
Multiply the 2nd equation by -1.
5x + 3y =11
-5x + 2y =1
Add like terms and solve.
5x + 3y =11
-5x + 2y = -1
5y =10
y =2
25.
5x + 3y = 11
5x = 2y + 1
STEP 4: Solve for the other variable by
substituting
into either equation.
5x + 3y =11
5x + 3(2) =11
5x + 6 =11
5x = 5
x =1
The solution to the system is (1,2).
26.
5x + 3y= 11
5x = 2y + 1
Step 5: Check the solution in both equations.
The solution to the system is (1,2).
5x + 3y = 11
5(1) + 3(2) =11
5 + 6 =11
11=11
5x = 2y + 1
5(1) = 2(2) + 1
5=4+1
5=5
27.
Solving Systems of Equations
using Elimination
Steps:
1. Place both equations in Standard Form, Ax + By = C.
2. Determine which variable to eliminate with Addition or
Subtraction.
3. Solve for the remaining variable.
4. Go back and use the variable found in step 3 to find the
second variable.
5. Check the solution in both equations of the system.
28.
Example #2:
x + y = 10
5x – y = 2
Step 1: The equations are already in standard
form: x + y = 10
5x – y = 2
Step 2: Adding the equations will eliminate y.
x + y = 10
x + y = 10
+(5x – y = 2)
+5x – y = +2
Step 3:
Solve for the variable.
x + y = 10
+5x – y = +2
6x = 12
x =2
29.
x + y = 10
5x – y = 2
Step 4:
Solve for the other variable by
substituting into either equation.
x + y = 10
2 + y = 10
y =8
Solution to the system is (2,8).
30.
x + y = 10
5x – y = 2
Step 5: Check the solution in both equations.
Solution to the system is (2,8).
x + y =10
2 + 8 =10
10=10
5x – y =2
5(2) - (8) =2
10 – 8 =2
2=2
31.
Using Elimination to Solve a Word
Problem:
Two angles are supplementary.
The measure of one angle is 10
degrees more than three times
the other. Find the measure of
each angle.
32.
Using Elimination to Solve a Word
Problem:
Two angles are supplementary.
The measure of one angle is 10
more than three times the other.
Find the measure of each angle.
x = degree measure of angle #1
y = degree measure of angle #2
Therefore x + y = 180
33.
Using Elimination to Solve a Word
Problem:
Two angles are supplementary.
The measure of one angle is 10
more than three times the other.
Find the measure of each angle.
x + y = 180
x =10 + 3y
34.
Using Elimination to Solve a Word
Problem, cont:
x + y = 180
x =10 + 3y
x + y = 180
x - 3y = 10
I will multiply the second equation by -1 then add like terms.
x + y = 180
-x + 3y = -10
4y =170
y = 42.5
35.
Using Elimination to Solve a Word
Problem:
Substitute the 42.5 to find the other
angle.
x + 42.5 = 180
x = 180 - 42.5
x = 137.5
(137.5, 42.5)
36.
Using Elimination to Solve a Word
problem:
The sum of two numbers is
70 and their difference is 24.
Find the two numbers.
x = first number
y = second number
Therefore, x + y = 70
37.
Using Elimination to Solve a Word
Problem:
The sum of two numbers is 70
and their difference is 24. Find
the two numbers.
x + y = 70
x – y = 24
38.
Using Elimination to Solve a Word
Problem:
x + y =70
x - y = 24
2x = 94
x = 47
47 + y = 70
y = 70 – 47
y = 23
(47, 23)
Be the first to comment